What is known about mindfulness and self-compassion among sport coaches? A scoping review - Hägglund, K.; Kenttä, G.; Wagstaff, C. R.; Bentzen, M. (International Sport Coaching Journal, 2025)
Mindfulness and self-compassion are two constructs positively related to well-being and mental health outside sport. Within sport, these constructs are emerging in research, yet the extant work has primarily been conducted with athlete samples. The aim of this scoping review was to provide a broad synthesis of the literature on mindfulness and self-compassion among coaches. Fourteen articles were included, 11 of them published 2019-2022. Of the 14 publications, the concepts studied were mindfulness (n = 10), self-compassion (n = 2), and a combination of both (n = 2). The samples were predominantly male coaches (68.7%), and most of the studies targeted coaches at the elite or competitive level. The most common area studied was developing and testing interventions and programs, followed by depicting relationships of mindfulness or self-compassion with desirable outcomes. This review significantly extends the current knowledge by illuminating critical issues in this rapidly moving area of research; the need for conceptual and contextual clarity of mindfulness and self-compassion; methodological considerations, such as measures that may allow reliable comparison across studies; and the need to further explore the potential benefits of mindfulness and self-compassion for coaches for sustainability and performance.